find the remainder when p is divided by q

p=2008^2007-2008 Q=2008^2+2009


The answer is 4032066.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Marco Brezzi
Sep 7, 2017

Let x = 2008 x=2008 , then

p ( x ) = 200 8 2007 2008 = x 2007 x p(x)=2008^{2007}-2008=x^{2007}-x

q ( x ) = 200 8 2 + 2009 = 200 8 2 + 2008 + 1 = x 2 + x + 1 = ( x ω ) ( x ω 2 ) q(x)=2008^2+2009=2008^2+2008+1=x^2+x+1=(x-\omega)(x-\omega^2)

Where ω \omega is the third root of unity e i 2 π 3 e^{i\frac{2\pi}{3}}

To find the remainder

p ( x ) = ( x ω ) ( x ω 2 ) h ( x ) + a x + b p(x)=(x-\omega)(x-\omega^2)h(x)+ax+b

Where h ( x ) h(x) is the quotient and a x + b ax+b is the remainder. Now, using the facts that 2007 2007 is a multiple of 3 3 and that ω \omega is a third root of unity

p ( ω ) = ω 2007 ω = 1 ω p(\omega)=\omega^{2007}-\omega=1-\omega

p ( ω 2 ) = ( ω 2 ) 2007 ω 2 = 1 ω 2 = ω + 2 p(\omega^2)=(\omega^2)^{2007}-\omega^2=1-\omega^2=\omega+2

Hence

p ( ω ) = ( ω ω ) ( ω ω 2 ) h ( ω ) + a ω + b = a ω + b p(\omega)=(\omega-\omega)(\omega-\omega^2)h(\omega)+a\omega+b=a\omega+b

p ( ω 2 ) = ( ω 2 ω ) ( ω 2 ω 2 ) h ( ω 2 ) + a ω 2 + b = ( ω + 1 ) a + b p(\omega^2)=(\omega^2-\omega)(\omega^2-\omega^2)h(\omega^2)+a\omega^2+b=-(\omega+1)a+b

{ 1 ω = a ω + b ω + 2 = ( ω + 1 ) a + b \Longrightarrow\begin{cases} 1-\omega=a\omega+b\\ \omega+2=-(\omega+1)a+b \end{cases}

a = 1 , b = 1 \Longrightarrow a=-1,b=1

The remainder is x + 1 -x+1 , substituting back x = 2008 x=2008

x + 1 = 2007 4032066 m o d ( 200 8 2 + 2009 ) -x+1=-2007\equiv \boxed{4032066}\mod (2008^2+2009)


Note:

ω 2007 = ( e i 2 π 3 ) 2007 = [ ( e i 2 π 3 ) 3 ] 669 = 1 669 = 1 \omega^{2007}=\left(e^{i\frac{2\pi}{3}}\right)^{2007}=\left[\left(e^{i\frac{2\pi}{3}}\right) ^3\right]^{669}=1^{669}=1

ω \omega is a root of x 2 + x + 1 x^2+x+1 , hence

ω 2 + ω + 1 = 0 ω 2 = ( ω + 1 ) \omega^2+\omega+1=0\Longrightarrow \omega^2=-(\omega+1)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...